The effect of laser remelting on the surface chemistry of Ti6al4V components fabricated by selective laser melting - Vaithilingam, Jayasheelan; Goodridge, Ruth D.; Hague, Richard J.M.; Christie, Steven D.R.; Edmondson, Steve (Elsevier, 2016)
Surface remelting/skin scanning of components is generally performed during the selective laser melting (SLM) process to improve the surface quality of a part. However, the chemical effects of surface remelting are not well understood. In this study, cuboidal parts fabricated with and without laser remelting were characterised using scanning electron microscopy (SEM), surface profilometry and X-ray photoelectron spectrophotometry (XPS). The SEM images showed a low-amplitude undulating pattern was observed on both surfaces. The surface chemistries of the surface remelted/skin scanned (SK) and non-surface remelted/non-skin scanned (NSK) samples were observed to significantly differ in their elemental composition. The thickness of the surface oxide layer of the SK surface was double that of the NSK surface. Also, the contribution of the major alloying elements, including titanium and aluminium, on the surface oxide layer varied for both NSK and SK surfaces. The surface chemistry of the NSK and SK surface was significantly different to a conventionally forged (CF) Ti6Al4V surface. The rate of decrease of oxide with depth was in the order of CF > NSK > SK. Although surface remelting is useful in rendering improved surface quality, its impact on surface chemistry should be carefully considered.